2014
DOI: 10.1186/s40529-014-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spermidine-induced changes at physiological and biochemical parameters levels in tomato seedling grown in saline-alkaline condition

Abstract: BackgroundTomato is one of the most popular vegetables, and middle tolerance for salt stress. Spermidine (Spd) has an important role in plant defense mechanisms against abiotic stress; however, relatively few data are available regarding Spd in responses of tomato to saline-alkaline stress. The effect of 0.25 mmol/L Spd on some physiological parameters of two tomato cultivars grown in 75 mmol/L saline-alkaline solutions were studied. Two cultivars are cv. Jinpeng chaoguan which is a highly salt-tolerant ecotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Significant increased amount of H2O2 (product of SOD activity) content generated in both the rice cultivars was imitated with increasing SOD activity at short-term NaCl stress when compared to the control plants, which subsequently necessitates the stimulation of H2O2 eliminating enzymes (CAT and APX) activities. The improved salt tolerance were highly correlated with increased activation of antioxidant enzymes in Arabidopsis, rice [30], wheat, tomato [24], soybean, maize [31], which is in accordance with our observations. Even many previous reports on genotype dependent accumulation of H2O2 content and differential response of antioxidative enzymes in salinity have been done in rice cultivars [32,33].…”
Section: Expression Profile Of Each Of the Antioxygenic Isoenzymessupporting
confidence: 90%
“…Significant increased amount of H2O2 (product of SOD activity) content generated in both the rice cultivars was imitated with increasing SOD activity at short-term NaCl stress when compared to the control plants, which subsequently necessitates the stimulation of H2O2 eliminating enzymes (CAT and APX) activities. The improved salt tolerance were highly correlated with increased activation of antioxidant enzymes in Arabidopsis, rice [30], wheat, tomato [24], soybean, maize [31], which is in accordance with our observations. Even many previous reports on genotype dependent accumulation of H2O2 content and differential response of antioxidative enzymes in salinity have been done in rice cultivars [32,33].…”
Section: Expression Profile Of Each Of the Antioxygenic Isoenzymessupporting
confidence: 90%
“…Previous research has shown that exogenous Spd enhanced the activities of antioxidants, including ascorbate peroxidase, superoxide dismutase (SOD), peroxidase (POD) and catalase in cucumber seedlings subjected to high temperatures (Tian et al ). Our previous study also showed that exogenous Spd significantly enhanced SOD and POD activities and decreased malondialdehyde, H 2 O 2 and superoxide anion (O 2 − ) levels under salinity–alkalinity stress (Zhang et al 2014). Exogenous Spd may, then, protect D1 protein from degradation by protecting plants from ROS, possibly by increasing the activity of scavengers.…”
Section: Discussionmentioning
confidence: 89%
“…The accumulation of soluble proteins in maize plants under high alkaline pressure may supply a storage form of nitrogen that is reutilized when stress is over ( Abdel Latef, 2010 ; Abdel Latef and Chaoxing, 2014 ; Zhang et al, 2014 ). The increase in soluble protein content of maize under the highest alkaline level applied was accompanied by a marked reduction in growth ( Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%